Water pollution: causes, negative effects and prevention methods - Kılıç, Zeyneb (İstanbul Sabahattin Zaim Üniversitesi, Fen Bilimleri Enstitüsü, 2021)
Water quality is a big issue that mankind is facing in recent years. Water is separated from other environmental components, because it is not substitutable. The water cycle constitutes the basic dynamics of the life and economy cycle. Water resources are limited and exposed to many human-induced negative effects. Fresh water resources on our planet constitutes only 2.5% of water resources. Water is an indispensable resource for all living things and it is a vital value. Life without water can not be considered. The existence of sufficient and good quality water is the basic condition of freshwater ecosystems as well as food security and sustainable development, and therefore the future of humanity. Pollution of the limited fresh water resources causes further pressure on fresh water resources. Eight liters of clean water must be used to clean one liter of the waste water. Safe drinking water is a indispensable need for all humans. The WHO reports that 80% diseases (bacterial, viral and parasitic) are waterborne. Human beings contribute in a great way to waste and pollute this vital natural resource. Education and raising awareness related to water pollution should be given to the humanity so that this problem can be reduced to a certain level. This research is about current scientific advances to cope with the water pollutants and focuses mainly on the source of different water pollutants and their current status in the environment and ecosysytem. It is thought that this study will contribute to the literature on the subject and to the reduction of the pollution level of water resources.
Su kirliliği nedenleri, olumsuz etkileri ve önleme yöntemleri
Zeyneb Kılıç, Adıyaman University, Faculty of Engineering, Civil Engineering Department, Adıyaman, Türkiye Corresponding author. E-mail address: zeynebboybay@gmail.com (Zeyneb Kılıç)
Keywords: Environment; Hydrology; Water; Water pollution